A Few Comments on the Employer’s Obligations Towards an Employee Unable to Perform His Current Job or Position in the Light of the Latest International Standards of Equal Treatment Regardless of Disability in Employment - Paluszkiewicz, Magdalena (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
The aim of the text is to engage in the discourse on the relationship between the legal regulations, which result from the employer’s obligations towards an employee who has become unable to perform his current job (Article 231 of the Labour Code) or has lost the ability to perform his current position (Article 14 of the Act on social and vocational rehabilitation and employment of disabled persons). It is justified to take up this issue again – on the one hand, by changing the concept of disability in the international standards of equal treatment in employment – on the other, by the case-law of the CJEU, which follows that the transfer to another workplace may also constitute an appropriate action taken in the performance of the obligation to provide reasonable accommodation to a worker with a disability. Thus, an attempt will be made to answer the question about the relationship of the latter obligation to the employer’s obligation as defined in the aforementioned regulations, and the analysis of the most important similarities and differences between them will enable the formulation of conclusions and de lege ferenda postulates.